2022
DOI: 10.1039/d2qm00106c
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal redox and optical stimuli can induce independent responses for catechol-chitosan films

Abstract: Catechol-based materials possess diverse properties that are especially well-suitable for redox-based bioelectronics. Previous top-down, systems-level property measurements have shown that catechol-polysaccharide films (e.g., catechol-chitosan films) are redox-active and allow electrons...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The fact that the counterions are soluble in the medium while the electrons are not soluble creates a complex linkage between electron and ion flow, and this linkage has been difficult to understand. Using MEP, we observed that melanin-containing films (like Cat–Chit films ,, ) are redox-active and can repeatedly exchange electrons with diffusible mediators. It remains to be seen if/how measured redox activities are related to ionic and electronic conductivities.…”
Section: Integrating Electrochemistry Into Materials Science and Biologymentioning
confidence: 99%
“…The fact that the counterions are soluble in the medium while the electrons are not soluble creates a complex linkage between electron and ion flow, and this linkage has been difficult to understand. Using MEP, we observed that melanin-containing films (like Cat–Chit films ,, ) are redox-active and can repeatedly exchange electrons with diffusible mediators. It remains to be seen if/how measured redox activities are related to ionic and electronic conductivities.…”
Section: Integrating Electrochemistry Into Materials Science and Biologymentioning
confidence: 99%
“…The melanin synthesized by these fungi is commonly either secreted or attached to the cell wall, making it a significant but often overlooked by‐product; and it is likely to be released into wastewater. Recognizing the numerous applications of melanin, [8] it presents itself as an abundant biological resource molecule with the potential for use in the circular economy.…”
Section: Introductionmentioning
confidence: 99%